Sei sulla pagina 1di 13

x y y = a + bx

x i y i

x =

P i x i

n

y = P i y i

n

Y = bX y y = b( x x)

b

f ( b) = ( bX i Y i ) 2

i

f ( b) = 2 ( bX i Y i ) X i = 0

i

= i ( X i Y i ) i X

2

i

y = bx + y bx

x i y i

10

16

17

30

15

23

16

26

16

24

14

20

11

14

12

15

15

21

18

26

20

35

y

y b = 2

xy

σ

x

σ

2

= 164

11

= 14 .91 = x

= 250

11

= 22 .73 = y

x i x

y i y

x i x) (y i y (x i x) 2

4.91

6.73

33.49

17.56

2.09

7.27

15.00

4.37

0.09

0.27

0.02

0.01

1.09

3.27

3.47

1.19

1.09

1.27

1.29

1.19

0.91

2.73

2.57

0.83

3.91

8.73

34.49

15.29

2.91

7.73

22.76

8.47

0.09

1.73

1.64

0.01

3.09

 

3.27

9.83

9.55

5.09

12.27

62.00

25.91

0

0

171.30

84.38

2

σ xy

2

σ x

y = 2 .03 x 7 .53